Self-Admission Training to Increase Confidence for Assisted Residents of Class II B Sorong Correctional Institution - Pia, Sonia Yuliers; Shofia, Adinda; Ekayani, Syafira Putri (Polteknik Ilmu Pemasyarakatan, 2024)
This study aims to determine the effect of self-acceptance training on increasing the confidence of prisoners of Class II B Sorong Prison who have served 2/3 (two thirds) of the criminal period. The research method used an experimental approach, with a quasi-experimental research design Non-Randomized the one group pretest and posttest. Researchers determined 20 prisoners as research subjects with low self-confidence. Using validated psychological scale instruments with Aiken's V range (V = 0.828 < 0.8), validated training modules with Aiken's V range (V = 0.82 < 0.8), observation sheets and Informed Consent. This study used the Independent Sample t Test analysis technique. The results showed that self-acceptance training was proven to increase the confidence of the prisoners, with the difference in training scores between T1 [M = 62.20, SD = 6.408, t = -10.734, sig (2-tailed) = 0.000 < 0.05] and T2 [M = 86.30, SD = 3.057, t = -10.734, sig (2-tailed) = 0.000 < 0.05]. Then in the control group showed T1 [M = 67.80, SD = 1.619, t = -10.433, sig (2-tailed) = 0.000 < 0.05] and T2 [M = 76.00, SD = 1.886, t = 10.433, sig (2-tailed) = 0.000 < 0.05]. It can be concluded that the research hypothesis is accepted where, the level of self-confidence of the experimental group is higher than the level of self-confidence of the control group.